HUBUNGAN ANTARA IN-SERVICE TRAINING DAN TINGKAT KEYAKINAN DIRI DOKTER UMUM DALAM PENGELOLAAN GANGGUAN JIWA DI GUNUNGKIDUL YOGYAKARTA - , Acub Zaenal Amoe, dr. Mubasysyir Hasanbasri, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Mental disorders experienced by approximately 25% of the entire population at least once in a period of time on their lifetime, and more than 40% of diagnosed inappropriately. General practitioners have a very important role in early detection and management of mental disorders. But the role is not running optimally. One of the reasons is lack of their self confidence in managing mental disorders. Literature study suggests that in-service training is a way to improve their skills in managing mental disorders. It is based on the assumption that during their education period, they had not got an adequate psychiatric knowledge as a capital in providing mental health services in primary health care and their private practice as well. Objective: To know the relationships between in-service training and general practitioners level of self confidence in managing mental disorders in Gunungkidul Yogyakarta. Methods: A descriptive, cross sectional analytic. The data analysis process began immediately after data collection. Questionnaires that had been collected and then processed with STATA program to get an overview of descriptive items of questions. Then look for relationships between related variables. Results: P values that higher than 0.05 found on the correlation between in-service training and level of confidence in the management of general practitioner mental disorder. Doctors who ever received previous in-service training had a higher level of confidence consecutive 5.8 X, 4X, and 2.9 X in terms of prescribing skills, doing counseling and conduct timely referrals with correct indications, than physicians group that never had training or additional formal education at all, but not in the diagnostic skill. There is potential for considerable stigma behavior towards patients with mental disorders among the doctors (approximately 30%). There were 87% of doctors believed in doing diazepam overprescribing, and 83% of them felt that their knowledge gained during lectures in medical faculty, was not enough as a capital to play a role in the community. Conclusion: no statistically significant correlation found between in-service training and general practitioners level of confidence in the management of mental disorder. Doctors who ever received previous in-service training appeared to have a higher confidence in prescribing psychotropic drugs, doing mental disorder counseling, doing timely referral actions with correct indications, but not in terms of diagnosis skills. The high perception of general practitioners that undergraduate training they get in College was very inadequate as a capital in providing service, became a justification that a qualified in-service training remains necessary in order to overcome the gap.